AKTIVITAS ANTIOKSIDAN METABOLIT SEKUNDER KAPANG ENDOFIT DAUN TANAMAN BAWANG DAYAK (ELEUTHERINE AMERICANA (AUBL.) MERR.) SECARA IN VITRO - Kumala, Shirly; Gabriel, Gabriel (Jurnal Farmasi Indonesia, 2019)
Bawang dayak is a medicine plant which has been known potential as an antioxidant. To isolate potential secondary metabolites as antioxidant needs many bawang dayak plants to be extracted. Utilization of endophytic microbes as a source of secondary metabolites will make the production of natural medicine raw materials is more efficient and environmentally friendly. This research was aimed to investigate secondary metabolites of endophytic fungi from bawang dayak leaves as antioxidant substance. The method of this research was a direct seed inoculating technique on the surface of Potato Dextrose Agar directly. Identification of fungi morphology by using macroscopic (visual) and microscopic (slide culture) method. The results of endophytic isolation of this research got four fungi isolates. Isolate is fermented with shake method, then it is extracted with ethyl acetate. The extract is continued for Antioxidant activity assessment used DPPH method. Secondary metabolite ethyl acetate extract of four isolates had a potention as antioxidant. Highest antioxidant activity was showed by ethyl acetate extract from d.IEP.4.2 isolate has IC50 at 82,9750 µg/mL which has been classified as strong antioxidant.